The Preparation and Property of Graphene /Tin Oxide Transparent Conductive Film - SUN Tao (Journal of Harbin University of Science and Technology, 2017)
Graphene doped tin oxide composites were prepared with SnCIZ·2HZ 0 and graphene oxide as raw materials with sol-gel method and then spincoated on the quartz glass to manufacture a new transparent conductive film. The composite film was characterized with X-ray diffraction(XRD)and scanning electron microscopy(SEM) analysis. XRD results show that the graphene oxide was successfully prepared with Hummers method. The graphene layers and particulate SnOZ can be clearly observed in SEM photos. The transmittance and conductivity of the thin films were tested with ultraviolet visible spectrophotometer and Hall effect measurement. The results show that the transmittivity of composite film in visible region is more than 90% and surface square resistance is 41 S2/口.The graphene/ SnOZ film exhibits a higher performance in transparence and conductivity than commercial FTO glass.